2020
DOI: 10.3389/fbioe.2020.583318
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Ptch1 by miR-342-5p and FoxO3 Induced Autophagy Involved in Renal Fibrosis

Abstract: The pathogenesis of renal fibrosis (RF) is not well understood. Here, we performed an integrative database analysis of miRNAs and mRNAs to discover the major regulatory pathway in RF. Putative miRNAs and mRNAs involved in RF in unilateral ureteral obstruction (UUO) model mice were extracted and analyzed using the Gene Expression Omnibus (GEO) database. The bioinformatics analysis suggested that Ptch1 expression is regulated by miR-342-5p and FoxO3. Then real-time PCR, Western blot, Fluorescence in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Furthermore, the mTORC1 signaling is able to stimulate the synthesis of proteins, lipids and nucleotides, thus inhibiting autophagy (Yuan et al, 2013 ). Autophagy dysfunction has been implicated in the pathogenesis of renal fibrosis (Zhao et al, 2019 ; Tang et al, 2020 ). TRIM proteins including TRIM6 (Mandell et al, 2014 ; Di Rienzo et al, 2020 ) have been link to the induction of autophagy.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the mTORC1 signaling is able to stimulate the synthesis of proteins, lipids and nucleotides, thus inhibiting autophagy (Yuan et al, 2013 ). Autophagy dysfunction has been implicated in the pathogenesis of renal fibrosis (Zhao et al, 2019 ; Tang et al, 2020 ). TRIM proteins including TRIM6 (Mandell et al, 2014 ; Di Rienzo et al, 2020 ) have been link to the induction of autophagy.…”
Section: Discussionmentioning
confidence: 99%
“…At present, many factors are believed to affect renal brosis, including myo broblasts, many cytokines, such as TGF-β, transcription factors, macrophages, and autophagy. The proposal of partial epithelial-mesenchymal transition (pMET) deepens our understanding of renal brosis [6][7][8][9][10][11]. An accurate assessment of the degree of renal brosis is important to patients' diagnosis, treatment, and e cacy judgment.…”
Section: Introductionmentioning
confidence: 99%
“…NRXN1 encodes a membrane protein that is interrelated with the transfer of Ca 2+ (11). Previous studies demonstrated that PTCH1 could induct the malignant cell stemness and facilitate the cell autophagy (12,13). SLC2A1 and SLC8A1 both belong to the solute carrier family.…”
Section: Discussionmentioning
confidence: 99%